Differences in stressful life events between men and women experiencing homelessness. Issue 2 (1st November 2020) - Rodriguez‐Moreno, Sara; Vázquez, José J.; Roca, Pablo; Panadero, Sonia
Abstract: People experiencing homelessness are particularly vulnerable to experiencing stressful life events (SLEs) at some point in their lives; these SLEs are crucial for understanding the etiology and maintenance of homelessness. This study analyses the differences between men and women experiencing homelessness in the suffering of SLEs throughout their lives (childhood, adolescence, and adulthood). The sample consisted of a group of 293 people experiencing homelessness in Madrid (Spain): 156 men and 137 women. The results suggest that the number and type of SLEs experienced by men and women are different. In general, women experiencing homelessness suffer more SLEs than men in all periods of their lives. The differences in the level of sexual violence in childhood, sexual abuse in adulthood, and abuse by a spouse or partner are particularly striking. However, men experiencing homelessness score significantly higher than women for alcohol abuse, police complaints, arrest, and imprisonment throughout their lives. These findings have significant implications for the design of interventions and social policies that should be tailored to the specific needs of men and women who are homeless.